(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper review health monitoring of concrete bridge by taking visual inspection and nondestructive test. In India most of bridges was constructed after 1950. So, Regular inspections and maintenance are the essential components of any bridge management program to ensure structural integrity and user safety. Health monitoring of bridge concept is widely applied to various forms of infrastructure, ranging from bridge to skyscraper. Health monitoring is used for detecting the existence of damage on the infrastructure, locating the damage, identifying the types of damage and quantifying the severity of damage. The area of health monitoring process that receives the most attention in the technical literature is the identification of data features that allow one to distinguish between the damage and undamaged structure. heavy traffic, the bridges are subjected to very high dynamic loading, to avoid Collapse Bridge it is mandatory to assess the conditions of existing bridge or health monitoring of bridge. Through this paper we were recommending corrective measure for operation and maintenance. NDT method is to be use for verification of visual inspection in bridge management where measure damage occurred in the structure but cannot determine by visual.